Angiofibroma/Trichoepithelioma - Bonifazi, E. (European Journal of Pediatric Dermatology, 2005)
Angiofibromas of tuberous sclerosis, which in the past were known as sebaceous adenomas due to their location in the middle of the face, may be not associated to neurological symptoms and signs. Due to their location, after puberty angiofibromas may be misdiagnosed as acne. Before puberty angiofibromas may be confused with multiple trichoepitheliomas.